Married with children: A collective labor supply model with detailed time use and intrahousehold expenditure information - Laurens Cherchye; Bram De Rock; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2010)
We propose a collective labor supply model with household production that generalizes an original model of Blundell, Chiappori and Meghir (2005). In our model, adults' individual preferences do not only depend on own leisure and individual private consumption of market goods. They also depend on the consumption of domestic goods, which are produced by combining goods bought at the market with individuals' time. We apply our model to new and unique data on Dutch couples with children. The data contains detailed information about the spouses' time use and the intrahousehold allocation of all expenditures. Our application uses a novel estimation strategy that builds upon the familiar two-stage allocation representation of the collective model. We obtain interesting (and plausible) empirical results. Spouses'; preferences depend on the consumption of domestically produced goods (including children's welfare). Next, Pareto weights depend on variables like the individual wages and the share in the household's nonlabor income. Finally, and perhaps surprisingly, we do not find evidence that mothers care more for their children than fathers.
Keywords: D11; D12; D13; 330; collective model; labor supply; time use; public goods; household production; Arbeitsangebot; Zeitallokation; Öffentliches Gut; Haushaltsproduktion; Familie-Beruf; Schätzung; Niederlande